Towards large-scale identification of HLA-restricted T cell epitopes from four vaccine candidate antigens in a malaria endemic community in Ghana. Issue 5 (31st January 2022) - Kusi, Kwadwo Asamoah; Ofori, Ebenezer Addo; Akyea-Mensah, Kwadwo; Kyei-Baafour, Eric; Frimpong, Augustina; Ennuson, Nana Aba; Belmonte, Maria; Ganeshan, Harini; Huang, Jun; Amoah, Linda Eva; Villasante, Eileen; Sedegah, Martha
Highlights: Plasmodium CSP and AMA1 exhibited more T cell epitopes compared to TRAP and CelTOS. The most frequent T cell responses to the four antigens were to the CSP C-terminal. Frequency of IFN-γ responses were 6-fold higher than that of granzyme B responses. Abstract: Sterile protection against clinical malaria has been achieved in animal models and experimental human challenge studies involving immunization with radiation attenuated Plasmodium falciparum sporozoite vaccines as well as by live sporozoites under chloroquine prophylaxis. Parasite-specific IFN-γ and granzyme B-secreting CD8 + T cells have been identified as key mediators of protection. Although the exact parasite targets of protective CD8 + T cell responses are not fully defined, responses against a handful of vaccine candidate antigens have been associated with protection. Identifying the T cell targets in these antigens will facilitate the development of simpler, cost-effective, and efficacious next generation multi-epitope vaccines. The aim of this study was to identify immunodominant portions of four malaria vaccine candidate antigens using peripheral blood mononuclear cells (PBMCs) from adults with life-long exposure to malaria parasites. Cryopreserved PBMCs from 291 HLA-typed subjects were stimulated with pools of overlapping 15mer peptides spanning the entire sequences of P. falciparum circumsporozoite protein (CSP, 9 pools), apical membrane antigen 1 (AMA1, 12 pools), thrombospondin related anonymous protein (TRAP, 6 pools) and cell traversal for ookinetes and sporozoites (CelTOS, 4 pools) in FluoroSpot assays. 125 of 291 subjects made IFN-γ responses to 30 of the 31 peptide pools tested and 22 of 291 made granzyme B responses, with 20 making dual responses. The most frequent responses were to the CSP C-terminal region and the least frequent responses were to TRAP and CelTOS. There was no association between FluoroSpot responses and active malaria infection, detected by either microscopy, RDT, or PCR. In conclusion, CSP and AMA1 have relatively higher numbers of epitopes that trigger IFN-γ and granzyme B-secreting T cells in adults with life-long malaria parasite exposure compared to the other two antigens tested, and highlights the continued relevance of these two antigens as vaccine candidates.